LONG-TERM DIETARY EFFECTS ON FRUIT FLY “LOVE STORY”: SIZE AND SYMMETRY OF SEX COMBS AND MALE MATING SUCCESS - S. Pavković-Lučić; D. Miličić; L. Lučić; V. Kekić (Journal of Animal and Plant Sciences, 2013)
The influence of three types of diets on the number and symmetry of sex comb teeth (male secondary sexual character) as well as on behavioral trait (mating success) was tested in fruit fly in laboratory conditions. Mating experiments were conducted with three Drosophila melanogaster strains reared more than one year on different food. The quality of the diet itself had no influence on the number of sex comb teeth, neither on their symmetry. The size of sex comb and levels of fluctuating asymmetry were similar in mated and unmated males. However, males developed on different substrates showed differences in mating success: males of the “banana strain” and of the “cornmeal strain” were more successful in achieving copulations than males of the “tomato strain”. It seems that some other traits (morphological, physiological, and behavioral) were more important for male mating success than tactile stimuli provided by sex combs during the courtship.
Keywords: Drosophila; nutrition; sex combs; mating behavior